Academics Human Capital Dan Kinerja Dosen Akuntansi : Studi Empiris Di Perguruan Tinggi Provinsi Banten - Rudiyanto Rudiyanto; Ade Jaya Sutisna (Politeknik Ganesha Medan, 2022)
This article focuses on the performance problems of accounting lecturers who reflect the performance of private universities in Banten province. The aims to provide empirical evidence regarding the relationship between the Academic Human Capital (knowledge, competence, dynamic capacities, working capacity, critical capacity) and the performance of accounting lecturers in private universities of Banten province. Data were collected using questionnaires sent personally to each accounting lecturer in Banten province. Individual lecturers used as units of analysis. Data obtained from 291 accounting lecturers were analyzed using partial least squares (PLS). This article reveals that academics human capital (AHC) with dimensions of knowledge, competency, and critics-capacity. Thus are the main factors in improving the performance of accounting lecturers efficiently and effectively. The Universities managed with higher AHC have a significant impact on lecturers' work (Tri Dharma Higher Education). This study offers College leaders several aspects related to the intangible assets (AHC) function, especially in developing their managerial performance. The provision of investment allocations for the three dimensions of the AHC can facilitate more effective managerial's decisions. The information of this research is helpful for universities to design and develop strategic policies in the long run.